MUATAN KEARIFAN LOKAL DALAM CERITA RAKYAT KEPULAUAN RIAU - Leoni, Tessa Dwi; Indrayatti, Wahyu (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
This study aims to describe: (1) local wisdom reflected in the folklore Kepulaun Riau viewed from the view of life (philosophy); (2) the local wisdom reflected in the Kepulauan Riau folklore is seen from the attitude of social life, counsel, and iktibar; (3) local wisdom reflected in Kepulauan Riau folklore as seen from ceremonies or traditional ceremonies; (4) the local wisdom reflected in the Kepulauan Riau folklore is seen from the principles, norms and rules of rule embodied into a social system; and (5) the local wisdom reflected in Kepulauan Riau folklore is seen from the habits, everyday behavior of social intercourse. The problem is analyzed based on folklore theory. The method used in this research is descriptive method of analysis. This object is collected by observation ; recording and interviews. Data analysis technique is done by content analysis technique. Based on the results of the study, folklore is still growing in Kepulauan Riau society. The folklore is so full of values. it also reflects local wisdom of local people who can show the pattern of customs and local cultural peculiarities. The findings of this study can be used as a basic backdrop for literary and cultural researchers to study the culture of Indonesia in general and Malay culture of Kepulauan Riau in particular. Furthermore, for the people of Kepulauan Riau itself, the findings is one of conservation efforts of Malay culture in Kepulauan Riau. In addition, the results of this study can be an alternative teaching materials, one of which can be arranged in Prosa Fiction textbook. Keywards: Local wisdom, Folklore, Kepulauan Riau